Study of the singular term in mixed adhesive joints. (July 2017) - Breto, Rubén; Chiminelli, Agustín; Lizaranzu, Miguel; Rodríguez, Rafael
Abstract: In the numerical modelling of mixed adhesive joints, where different materials are disposed along the bond-lines, trimaterial singularities may arise at the adhesive bands transition points, resulting in mesh-dependent models. This work is focused on the study, characterization and treatment of these type of singularities. Firstly, the selection of an intermediate adhesive material for generating a tailored transition between bands is addressed, using analytical solutions and then corroborating by means of a novel technique for determining the influence distance of the singularity with the finite element method as calculation tool. Furthermore, it is proved how a continuum material field transition between bands produces a convergent finite element solution applying the considerations of this framework (analytical asymptotic solutions). Finally, in order to achieve the best numerical convergence rate in the models, the optimum material transition function is obtained and checked through FEM.